1998
DOI: 10.1046/j.1432-1327.1998.2580696.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of a rhamnan and a fucorhamnan, both present in the lipopolysaccharide of Burkholderia vietnamiensis strain LMG 10926

Abstract: The polymeric fraction isolated after mild acid hydrolysis of the lipopolysaccharide (LPS) from Burkholderia vietnamiensis strain LMG 10926 contained L‐rhamnose (Rha) and D‐fucose (Fuc). From NMR studies supported by the results of methylation analysis and Smith degradation, it could be inferred that the material was probably a mixture of two glycans. One component was a linear rhamnan with a trisaccharide repeating unit (1); the other was a branched fucorhamnan with a tetrasaccharide repeating uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…is attributed to α‐ d ‐ N ‐acetylglucosamine. The two remaining major anomeric resonances are determined to be β‐ l ‐rhamnose (Jann et al ., 1993; Knirel et al ., 1996; Bartodziejska et al ., 1998; Gaur et al ., 1998; Gunawardena et al ., 1998; Shashkov et al ., 2000b) and β‐ d ‐galacturonic acid (Bartodziejska et al ., 1998; Gunawardena et al ., 1998; Knirel et al ., 2000; Stroop et al ., 2002). The minor anomeric resonance at 103.29 p.p.m.…”
Section: Resultsmentioning
confidence: 99%
“…is attributed to α‐ d ‐ N ‐acetylglucosamine. The two remaining major anomeric resonances are determined to be β‐ l ‐rhamnose (Jann et al ., 1993; Knirel et al ., 1996; Bartodziejska et al ., 1998; Gaur et al ., 1998; Gunawardena et al ., 1998; Shashkov et al ., 2000b) and β‐ d ‐galacturonic acid (Bartodziejska et al ., 1998; Gunawardena et al ., 1998; Knirel et al ., 2000; Stroop et al ., 2002). The minor anomeric resonance at 103.29 p.p.m.…”
Section: Resultsmentioning
confidence: 99%
“…Assignments of the other signals were completed by means of the 1 H-1 H COSY and 1 H-13 C HMQC spectra, and also by comparison with the chemical shift data of similarly substituted sugar residues (Gargiulo et al, 2008;Gaur, Galbraith, & Wilkinson, 1998;Senchenkova, Shashkov, Laux, Knirel, & Rudolph, 1999). From the 1 H-13 C HMQC spectrum, the correlated signals of H-3 at ı 3.93 ppm and C-3 at ı 79.2 ppm were ascribed to the linkage sites of the (1 → 3)-linked rhamnopyranose, and the shoulder signals of the H-3 at ı 3.96 ppm with its related C-3 at ı 79.2 ppm suggested that the protons had different environments in the structure, and it was assigned to the (1 → 2,3)-linked rhamnopyranose.…”
Section: Nmr Analysis Of the Desulfated Polysaccharide Dspmlmentioning
confidence: 99%